Liquid crystal orientation agent, liquid crystal orientation film and liquid crystal display element
By using a diamine compound with a specific structure to polymerize with a tetracarboxylic dianhydride monomer to prepare a liquid crystal alignment agent, the anchoring ability of the liquid crystal alignment film is enhanced, the problem of insufficient anchoring of the polyimide liquid crystal alignment film is solved, and a more stable liquid crystal orientation and better display performance are achieved.
Patent Information
- Application Number
- CN202510577893.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-09-16
AI Technical Summary
The existing polyimide liquid crystal alignment film has insufficient anchoring ability for liquid crystals, resulting in unstable alignment effect, poor pretilt angle stability, and poor reliability performance.
Polyamic acid and its derivatives prepared by polymerizing diamine compounds of specific structures with tetracarboxylic dianhydride monomers are used as liquid crystal alignment agents to enhance the anchoring ability of the liquid crystal alignment film and make the liquid crystal orientation more uniform and stable through photoalignment or friction alignment.
The invention improves the stability and reliability of the pre-tilt angle of the liquid crystal alignment film, reduces AC afterimage, enhances the contrast and response speed of the liquid crystal display, and improves the display effect.
Smart Images

Figure BDA0005389407410000021 
Figure BDA0005389407410000031 
Figure BDA0005389407410000032
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of liquid crystal display technology, and in particular relates to a liquid crystal alignment agent, a liquid crystal alignment film and a liquid crystal display element with good reliability performance. Background Art
[0002] Liquid crystal displays (LCDs) are currently widely used as thin, lightweight display devices. The display characteristics of LCDs are significantly affected by the orientation of the liquid crystals, the size and stability of the pretilt angle, and electrical properties. To improve these display characteristics, not only the selected liquid crystal material is crucial, but also the liquid crystal alignment film material, which is in direct contact with the liquid crystal material and determines its orientation.
[0003] Liquid crystal alignment film materials are the foundation of liquid crystal molecular alignment technology and a crucial enabler for new LCD display modes. Common display modes include TN (twisted nematic), IPS (in-plane switching), VA (vertical alignment), and OCB (optically compensated bend alignment). Existing LCD panel manufacturing processes (from the first-generation G1 to the eleventh-generation G11 production lines) primarily utilize polyimide (PI) as the alignment film. After treatment, this surface produces anisotropy in molecular orientation, inducing "anchoring" of the liquid crystal molecules, leading to their alignment under the influence of an electric field. Polyimide, as a liquid crystal alignment agent, offers numerous advantages: PI film inherently orients liquid crystal molecules; exhibits excellent alignment effects on all liquid crystal materials, making it more suitable than other alignment materials; is easily processed and can be applied by rotation, rolling, spraying, or gravure coating, depending on the substrate size; does not chemically react with liquid crystal molecules; exhibits strong adhesion to the substrate; and exhibits strong hydrophobicity. However, the anchoring ability of the existing PI liquid crystal alignment film on liquid crystals needs to be enhanced, the alignment effect of the PI liquid crystal alignment film is not stable enough, and the stability of the pretilt angle is poor, resulting in poor reliability of the alignment film. Summary of the Invention
[0004] In view of this, the present invention provides a liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element with excellent reliability. By using polyamic acid and its derivatives obtained from diamine compounds with specific structures as raw materials as liquid crystal alignment agents, the present invention can effectively enhance the liquid crystal alignment film's ability to anchor liquid crystals, resulting in a highly stable alignment effect without defects, excellent pretilt angle stability, and excellent reliability.
[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] In a first aspect, the present invention provides a liquid crystal alignment agent, comprising: a polymer (A) and a solvent (B). The polymer (A) is obtained by reacting a mixture, the mixture comprising a tetracarboxylic dianhydride component (a) and a diamine component (b). The diamine component (b) comprises an alignment structure diamine (b-1) and a base diamine (b-2), wherein the alignment structure diamine (b-1) is selected from any one or combination of compounds represented by formula (1), formula (2), and / or formula (3):
[0007]
[0008] Wherein, R7 each independently represents any one or combination of -O-, -COO, -OCH2, -COOCH2, -CH2OCO, -CH2O, -NHCO, -CONH, -N(CH3)CO, olefin, alkyne, benzene ring, cyclohexane and / or imide ring; preferably, R7 each independently represents any one or combination of -O-, -COO, -NHCO, -CONH, benzene ring, cyclohexane and / or imide ring. R8 each independently represents an alkyl chain with a carbon number of 1 to 50. S1 each independently represents any one or combination of the structures represented by formula (S-1) and / or formula (S-2);
[0009]
[0010] Furthermore, the tetracarboxylic dianhydride component (a) is selected from any one or combination of the compounds represented by formula (a-1) and / or formula (a-2);
[0011]
[0012] Wherein, G1 is an aliphatic, alicyclic or aromatic organic group.
[0013] Furthermore, the base diamine (b-2) is selected from at least one compound represented by formula (4):
[0014]
[0015] Wherein, X1 and X2 independently represent any one or a combination of a hydrogen atom, an alkyl chain having 1 to 10 carbon atoms, an alkenyl chain having 2 to 10 carbon atoms, and an alkynyl chain having 2 to 10 carbon atoms; and Z1 is a divalent organic group. From the perspective of liquid crystal orientation, X1 and X2 are preferably hydrogen atoms or methyl groups.
[0016] Furthermore, the polymer (A) is any one or a combination of polyimide, polyamic acid and polyamic acid ester. Based on the total weight of the liquid crystal alignment agent as 100 weight%, the weight percentage of the polymer (A) is 1-15%, preferably 1-8%, and more preferably 1.5-7%.
[0017] The preparation method of the polyamic acid can be a conventional method, comprising the following steps: dissolving a base diamine and an alignment structure diamine in a polar aprotic solvent in sequence, adding a tetracarboxylic dianhydride monomer after sufficient dissolution, and conducting a polymerization reaction at a temperature of 0°C to 80°C for 1 to 24 hours. After the reaction is completed, the solution is diluted with a polar aprotic solvent and additives such as a leveling agent to obtain a viscous and transparent polyamic acid solution. The molar ratio of the diamine component (b) to the tetracarboxylic dianhydride component (a) is 100:(80-100). It is understood that the ratio of the diamine component (b) to the tetracarboxylic dianhydride component (a) is used to adjust the viscosity, preferably 100:(90-100), and optimally 100:(95-100). The molar ratios of the different diamines in the diamine component (b) relative to the total diamine content are as follows: the base diamine is 0.01% to 100%, preferably 10% to 100%, and most preferably 50% to 100%; the alignment structure diamine is 0.01% to 50%, preferably 1% to 50%, and most preferably 1% to 30%. The polymerization temperature is preferably 20°C to 60°C, and the reaction time is preferably 2 to 12 hours. The reaction solids content is 10% to 50%, preferably 12% to 40%, and most preferably 15% to 30%.
[0018] Wherein, the chemical structural formula of the polyimide is as follows:
[0019]
[0020] Wherein, n≥1, preferably n=10-500, more preferably n=50-400, most preferably n=100-300; A represents a dianhydride residue, B represents a basic diamine residue, and C represents an alignment structure diamine residue.
[0021] In the above structural formula, it can be understood that the base diamine serves as the basis for synthesizing the polyimide, and different structures can be selected to adjust the bulk resistance. The alignment diamine functions to provide alignment properties for the polyimide. After photoalignment, the synthesized polyimide can align the liquid crystal, resulting in a certain pretilt angle in the liquid crystal cell.
[0022] The preparation method of the above-mentioned polyimide can adopt a conventional method, comprising the following steps: heating the polyamic acid prepared by the above-mentioned method for preparing polyamic acid in the presence of a dehydrating agent and a catalyst. During this process, the amic acid functional group in the polyamic acid is converted into an imide group through an imidization reaction. The above-mentioned polyimide can be a completely imidized product obtained by completely dehydrating and ring-closing the amic acid structure possessed by the polyamic acid or the amic acid ester structure possessed by the polyamic acid ester, or it can be a partial imidized product obtained by dehydrating and ring-closing only a part of the amic acid or amic acid ester structure to obtain a coexistence of an amic acid structure or an amic acid ester structure and an imide ring structure. For the polyimide used in the present invention, the weight ratio of the polyamic acid to the imidization reaction solvent is preferably 1: (5 to 30), and the imidization rate is preferably 20% or more. From the perspective of ensuring solubility relative to the solvent, it is preferably 90% or less, and more preferably 60% or less. The temperature of the imidization reaction is 0 to 100°C, preferably 20 to 60°C; the reaction time is 1 to 120 hours, preferably 2 to 30 hours. The dehydrating agent can be selected from an acid anhydride compound, such as acetic anhydride, propionic anhydride or trifluoroacetic anhydride; the molar ratio of the polyamic acid to the dehydrating agent is 1:(1 to 10). The catalyst can be selected from pyridine, trimethylamine or triethylamine; the molar ratio of the dehydrating agent to the catalyst is 1:(0.1 to 5). The imidization rate is a value expressing the ratio of the total number of amic acid structures or amic acid ester structures to the number of imide ring structures in the polyimide as a percentage. Here, a part of the imide ring may be an isoimide ring.
[0023] Furthermore, the solvent (B) is a polar aprotic solvent, comprising any one or a combination of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, m-cresol and / or tetrahydrofuran; the weight percentage of the solvent (B) is 0 to 100%.
[0024] From the perspective of improving the durability of the liquid crystal alignment film, the liquid crystal alignment agent of the present invention may further contain an epoxy compound as a component other than the polymer (A). The epoxy compound serves to improve the adhesion between the liquid crystal alignment film and the substrate. The epoxy compound is preferably at least one compound represented by formula (Y);
[0025]
[0026] Among them, R 10 Each is independently selected from any one or combination of a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, and / or a phenyl group. 11Each independently selected from any one or combination of a hydrogen atom and an alkyl group having 1 to 6 carbon atoms, R 11 Preferably it is a hydrogen atom. 12 are independently selected from monovalent or divalent organic groups. n is an integer of 1 to 6. The following compounds of formula (Y-1) to formula (Y-5) are preferred examples of the epoxy compound.
[0027]
[0028] When an epoxy compound is used, based on 100 weight % of the total amount of the liquid crystal alignment agent, the weight percentage of the compound represented by formula (Y) is 1 to 30 weight %, preferably 2 to 20 weight %, more preferably 2 to 15 weight %, and further preferably 2 to 10 weight %.
[0029] From the perspective of improving the coating properties of the liquid crystal alignment agent, the liquid crystal alignment agent of the present invention may further contain a leveling agent represented by the following structural formula:
[0030]
[0031] Among them, R 13 Any one or combination independently selected from alkyl groups having 1 to 12 carbon atoms. 14 Any one or a combination of -OH and -O. Examples include ethyl acetate, ethylene glycol monobutyl ether, diethylene glycol diethyl ether, diacetone alcohol, and ethylene glycol butyl ether acetate. When a leveling agent is used, the amount of the leveling agent used is 0 to 80% based on 100% by weight of the total amount of the liquid crystal alignment agent.
[0032] The solvent used in the polymerization reaction and the solvent used in the imidization reaction may be the same as or different from the solvent (B) in the liquid crystal alignment agent. There are no particular restrictions on the solvent used in the polymerization reaction and the solvent used in the imidization reaction, as long as they can dissolve the reactants. Examples include N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, m-cresol, and tetrahydrofuran.
[0033] Compared with the prior art, the liquid crystal alignment agent of the present invention is formed by polymerizing a diamine with a specific structure containing a piperazine or piperidine group and a tetracarboxylic dianhydride monomer. Since the diamine used contains a piperazine or piperidine group with a specific structure, the anchoring ability of the liquid crystal alignment film for the liquid crystal is effectively enhanced. After optical alignment or friction orientation, the liquid crystal orientation can be made more uniform and stable, without any defects and with excellent pretilt angle stability, excellent reliability, and no residual voltage is easily accumulated. The backlight source resistance and high temperature and high humidity performance are good, thereby making it possible to prepare high-quality display elements and obtain a higher yield rate.
[0034] In a second aspect, the present invention provides a liquid crystal alignment film comprising the liquid crystal alignment agent described above. The liquid crystal alignment film comprises the liquid crystal alignment agent of the present invention, which is polymerized from a diamine containing a specific piperazine or piperidine group and a tetracarboxylic dianhydride monomer. Because the diamine contains the piperazine or piperidine group of the specific structure, the liquid crystal alignment film effectively enhances its ability to anchor the liquid crystal, resulting in more uniform and stable alignment of the liquid crystal molecules, an increased pretilt angle, and excellent antistatic properties. The display exhibits a fast response speed, good contrast, and excellent afterimage performance.
[0035] In a third aspect, the present invention provides a liquid crystal display element comprising the liquid crystal alignment film described above. A method for preparing the liquid crystal display element comprises the following steps: preparing two substrates, each having a liquid crystal alignment film, and filling the space between the two substrates with liquid crystal to form a liquid crystal cell. The liquid crystal alignment film produced using the liquid crystal alignment agent of the present invention is suitable for both photo-alignment and rubbing-alignment. Liquid crystal display elements produced using the liquid crystal alignment agent of the present invention are suitable for various types of liquid crystal display elements.
[0036] Compared with the prior art, the liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element proposed in the present invention have the following advantages:
[0037] (1) The liquid crystal alignment agent of the present invention contains a diamine residue with an alignment structure having a specific piperazine or piperidine group, which enhances the anchoring ability of the liquid crystal alignment film to the liquid crystal. After optical alignment or rubbing alignment, the liquid crystal alignment film of the present invention makes the liquid crystal orientation more uniform and stable, effectively reducing the AC afterimage level caused by insufficient anchoring force of the LCD panel, thereby improving the contrast of the LCD panel and effectively improving the display effect of the liquid crystal display;
[0038] (2) The diamine monomer with a specific piperazine or piperidine group used in the liquid crystal alignment agent of the present invention has good electron conduction ability, which can accelerate the dissipation of the DC bias charge in the LCD box and alleviate the afterimage and flicker problems caused by the accumulation of DC bias charge on the LCD panel;
[0039] (3) The preparation method of the liquid crystal alignment agent of the present invention is simple and has broad market prospects. The liquid crystal alignment film prepared thereby has a stable orientation effect, no adverse defects, and excellent pretilt angle stability. It has excellent reliability and is suitable for large-scale promotion and application. DETAILED DESCRIPTION
[0040] The following is a clear and complete description of the technical solutions of the present invention in conjunction with the embodiments of the present application. Obviously, the embodiments described are part of the embodiments of the present application, not all of them. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0041] The term "arbitrary" used in chemical formula definitions means "not only the position but also the number can be freely selected." For example, the expression "arbitrary A can be substituted with B, C, D, or E" means that one A can be substituted with B, C, D, or E, and any one of multiple As can be substituted with any one of B, C, D, or E. It also means that at least two of A substituted with B, A substituted with C, A substituted with D, and A substituted with E can be present in combination. However, when any -CH2- group can be substituted with another group, this does not include the case where multiple consecutive -CH2- groups are substituted with the same group.
[0042] A substituent that is not explicitly bonded to any of the carbon atoms constituting the ring means that the bonding position is free within a range that does not cause any chemical problem.
[0043] The use of the same symbol in multiple chemical formulas indicates that the groups have the same definition, but does not necessarily mean that they are the same group in all chemical formulas. In this case, the same group can be selected in multiple chemical formulas, or different groups can be selected in each chemical formula. In this case, when multiple identical symbols are used in a single chemical formula, the multiple groups may all be different from the groups in other chemical formulas, or only some may be different.
[0044] In the chemical formula, Me represents a methyl group, and Et represents an ethyl group.
[0045] Unless otherwise specified, all temperatures herein are in degrees Celsius. The components used in the following examples and comparative examples are compounds known in the art and can be synthesized by known methods or obtained through commercial channels. These synthesis techniques are also conventional.
[0046] Liquid crystal alignment agent
[0047] The present invention provides a liquid crystal alignment agent, which comprises: a polymer (A) and a solvent (B). In addition, the liquid crystal alignment agent may further comprise an additive (C) as required.
[0048] Hereinafter, each component of the liquid crystal alignment agent used in the present invention will be described in detail.
[0049] Gold-polymer (A)
[0050] The polymer (A) is any one or a combination selected from polyimide, polyamic acid, and polyamic acid ester. When the total amount of the liquid crystal aligning agent is 100 wt %, the polymer (A) is 1 to 15 wt %, preferably 1 to 8 wt %, and more preferably 1.5 to 7 wt %.
[0051] The polyimide, polyamic acid, and polyamic acid ester in polymer (A) are all prepared by reacting a mixture comprising a tetracarboxylic dianhydride component (a) and a diamine component (b). The tetracarboxylic dianhydride component (a), the diamine component (b), and the method for preparing polymer (A) are described below.
[0052] Tetracarboxylic dianhydride component (a)
[0053] The tetracarboxylic dianhydride component (a) is selected from at least one compound represented by formula (a-1) and / or formula (a-2):
[0054]
[0055] Wherein, G1 is an aliphatic, alicyclic or aromatic organic group. As the tetracarboxylic dianhydride represented by the above formula (a-1) and formula (a-2), compounds represented by formula (G-1) to formula (G-43) can be mentioned, but are not limited to these compounds.
[0056]
[0057]
[0058]
[0059] Wherein, n in formula (G-19) is an integer from 0 to 20;
[0060]
[0061]
[0062]
[0063] In formulas (G-3), (G-40), and (G-43), R9 represents any one or a combination of a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, and / or a phenyl group. The number of R9 in formulas (G-3) and (G-40) is 0 to 4, the number of R9 in formula (G-41) is 0 to 5, the number of R9 in formula (G-42) is 0 to 6, and the number of R9 in formula (G-43) is 0 to 6.
[0064] Based on the total usage amount of the diamine component (b) being 100 mol, the usage amount of the tetracarboxylic dianhydride component (a) is 80 to 100 mol, preferably 90 to 100 mol, and more preferably 95 to 100 mol. The ratio range of the diamine component (b) to the tetracarboxylic dianhydride component (a) serves to adjust the viscosity.
[0065] In the embodiment of the present invention, the formula (G-28) and the formula (G-40) are used as the structural design, and the ratio is 0.01 to 100 mol%, preferably 50 to 100 mol%, and most preferably 80 to 100 mol%. At the same time, the present invention can also be used with other tetracarboxylic dianhydrides to adjust the bulk resistance. For high resistance (greater than 1×10 14 ), preferably Formula (G-1) to Formula (G-4), Formula (G-7) to Formula (G-13), Formula (G-22). For low resistance (less than 1×10 14 ), preferably Formula (G-5), Formula (G-6), Formula (G-14) to Formula (G-21), Formula (G-23) to Formula (G-43).
[0066] Diamine component (b)
[0067] The diamine component (b) includes an alignment structure diamine (b-1) and a base diamine (b-2).
[0068] The alignment structure diamine (b-1) is selected from at least one of the compounds represented by formula (1), formula (2) and / or formula (3):
[0069]
[0070] Wherein, R7 each independently represents any one or combination of -O-, -COO, -OCH2, -COOCH2, -CH2OCO, -CH2O, -NHCO, -CONH, -N(CH3)CO, olefin, alkyne, benzene ring, cyclohexane, and / or imide ring; preferably, R7 each independently represents any one or combination of -O-, -COO, -NHCO, -CONH, benzene ring, cyclohexane, and / or imide ring. R8 each independently represents an alkyl chain with a carbon number of 1 to 50. S1 each independently represents at least one of the structures represented by formula (S-1) and formula (S-2):
[0071]
[0072] The present invention uses the above monomers as structural design, and their main function is to impart alignment properties to the PI film. In the diamine component (b) of the present invention, the molar ratio of the alignment structure diamine to the total diamine is 0.01 to 50 mol%, preferably 1 to 50 mol%, and more preferably 1 to 30 mol%.
[0073] The base diamine (b-2) is selected from at least one compound represented by formula (4):
[0074]
[0075] Wherein, X1 and X2 independently represent any one or a combination of a hydrogen atom, an alkyl chain having 1 to 10 carbon atoms, an alkenyl chain having 2 to 10 carbon atoms, and / or an alkynyl chain having 2 to 10 carbon atoms; and Z1 is a divalent organic group. From the perspective of liquid crystal orientation, X1 and X2 are preferably hydrogen atoms or methyl groups. Examples of the structure of Z1 include those shown in the following formulas (Z-1) to (Z-193).
[0076]
[0077]
[0078] Wherein, n in formula (Z-28) is an integer from 2 to 10;
[0079]
[0080]
[0081]
[0082]
[0083] Wherein, in formula (Z-92) and formula (Z-93), n is an integer from 2 to 10;
[0084]
[0085] Wherein, in formula (Z-96), R2 is independently selected from F, Cl, Br, I, CH3, CF3, CN, and benzene ring, and the number thereof is 0 to 8;
[0086]
[0087] Wherein, n in formula (Z-97) is an integer from 2 to 10;
[0088]
[0089]
[0090] Wherein, n in formula (Z-116) is an integer from 0 to 20;
[0091]
[0092] Wherein, in formula (Z-118), n is an integer from 0 to 20;
[0093]
[0094] Wherein, in formula (Z-123), R3 represents F, Cl, Br, I, CH3, CF3, CN, or a benzene ring, and the number thereof is 1;
[0095]
[0096] Wherein, n in formula (Z-129) is an integer from 0 to 20;
[0097]
[0098] Wherein, in formula (Z-130) and formula (Z-131), n is an integer of 0-20; in formula (Z-131), R4 is independently selected from F, Cl, Br, I, CH3, CF3, CN, and a benzene ring, and the number thereof is 1;
[0099]
[0100] Wherein, R5 in formula (Z-138) is independently selected from F, Cl, Br, I, CH3, CF3, CN, and benzene ring, and the number thereof is 1 to 2.
[0101]
[0102]
[0103]
[0104] Wherein, n in formula (Z-156) is an integer from 1 to 5;
[0105]
[0106] Wherein, n in formula (Z-161) is an integer from 1 to 5;
[0107]
[0108] Wherein, n in formula (Z-166) is an integer from 1 to 20;
[0109]
[0110] Wherein, R6 in formula (Z-174) is independently selected from any one or combination of -COO, -OCO, -NHCO, -N(CH3)CO, and benzene ring, and the number thereof is 1 to 2.
[0111]
[0112] Wherein, n in formula (Z-182) is an integer from 0 to 20;
[0113]
[0114]
[0115] In the above-mentioned basic diamine (b-2), different structures can be selected from the polyimide precursor or the polyimide obtained by imidizing the polyimide precursor to adjust the bulk resistance. 14 ), preferably Formula (Z-1) to Formula (Z-10), Formula (Z-13) to Formula (Z-19), Formula (Z-29) to Formula (Z-30), Formula (Z-41) to Formula (Z-42), Formula (Z-49) to Formula (Z-50), Formula (Z-52) to Formula (Z-57), Formula (Z-61) to Formula (Z-62), Formula (Z-64) to Formula (Z-72), Formula (Z-98) to Formula (Z-105), Formula (Z-10 7) to Formula (Z-109), Formula (Z-113) to Formula (Z-115), Formula (Z-124) to Formula (Z-128), Formula (Z-134) to Formula (Z-135), Formula (Z-145) to Formula (Z-150), Formula (Z-158) to Formula (Z-160), Formula (Z-162) to Formula (Z-163), Formula (Z-173) to Formula (Z-174), Formula (Z-191) to Formula (Z-193). For low resistance (less than 1×10 14 ), preferably formula (Z-11) to formula (Z-12), formula (Z-20) to formula (Z-28), formula (Z-31) to formula (Z-40), formula (Z-43) to formula (Z-48), formula (Z-51), formula (Z-58) to formula (Z-60), formula (Z-63), formula (Z-73) to formula (Z-97), formula (Z-106), formula (Z-110) to formula (Z-112), formula (Z-116) to formula (Z-123), formula (Z-129) to formula (Z-133), formula (Z-136) to formula (Z-144), formula (Z-151) to formula (Z-157), formula (Z-161), formula (Z-164) to formula (Z-172), and formula (Z-175) to formula (Z-190).
[0116] In the examples of the present invention, formula (Z-1) and formula (Z-11) are used as the base diamine, but the present invention is not limited to the selection of the base diamine. In the diamine component (b) of the present invention, the base diamine accounts for 0.01 to 100 mol% of the total diamine molar ratio, preferably 10 to 100 mol%, and more preferably 50 to 100 mol%.
[0117] Method for preparing polymer (A)
[0118] The polymer (A) is any one or a combination of polyimide, polyamic acid and / or polyamic acid ester. The preparation methods of the above-mentioned various polymers are further described below.
[0119] Method for preparing polyamic acid
[0120] The preparation method of the polyamic acid can be prepared by a conventional method, comprising the following steps: dissolving the base diamine and the alignment structure diamine in a polar aprotic solvent in sequence, adding the tetracarboxylic dianhydride monomer after sufficient dissolution, and carrying out a polymerization reaction at a temperature of 0°C to 80°C for 1 to 24 hours. After the reaction is completed, the solution is diluted with a polar aprotic solvent and additives such as a leveling agent to obtain a viscous and transparent polyamic acid solution. In this process, the diamine component (b) or the tetracarboxylic dianhydride component (a) designed with different resistance values is adjusted to participate in the reaction to obtain polyamic acid. The molar ratio of the diamine component (b) to the tetracarboxylic dianhydride component (a) is 100: (80-100). It can be understood that the ratio range of the diamine component (b) to the tetracarboxylic dianhydride component (a) is used to adjust the viscosity, preferably 100: (90-100), and more preferably 100: (95-100). The molar ratios of the different diamines in the diamine component (b) relative to the total diamine content are as follows: 0.01% to 100% of the base diamine, preferably 10% to 100%; 0.01% to 50% of the alignment structure diamine, preferably 1% to 50%, and more preferably 1% to 30%. The polymerization temperature is preferably 20°C to 60°C, and the reaction time is preferably 2 to 12 hours. The reaction solids content is 10% to 50%, preferably 12% to 40%, and more preferably 15% to 30%.
[0121] Method for preparing polyimide
[0122] The chemical structural formula of the polyimide is as follows:
[0123]
[0124] Wherein, n≥1, preferably n=10-500, more preferably n=50-400, most preferably n=100-300; A represents a dianhydride residue, B represents a basic diamine residue, and C represents an alignment structure diamine residue.
[0125] In the above structural formula, it can be understood that the base diamine serves as the basis for synthesizing the polyimide, and different structures can be selected to adjust the bulk resistance. The alignment diamine functions to provide alignment properties for the polyimide. After photoalignment, the synthesized polyimide can align the liquid crystal, resulting in a certain pretilt angle in the liquid crystal cell.
[0126] The preparation method of the above-mentioned polyimide can adopt a conventional method, comprising the following steps: heating the polyamic acid prepared by the above-mentioned method for preparing polyamic acid in the presence of a dehydrating agent and a catalyst. During this process, the amic acid functional group in the polyamic acid is converted into an imide group through an imidization reaction. The above-mentioned polyimide can be a completely imidized product obtained by completely dehydrating and ring-closing the amic acid structure possessed by the polyamic acid or the amic acid ester structure possessed by the polyamic acid ester, or it can be a partial imidized product obtained by dehydrating and ring-closing only a part of the amic acid or amic acid ester structure to obtain a coexistence of an amic acid structure or an amic acid ester structure and an imide ring structure. For the polyimide used in the present invention, the weight ratio of the polyamic acid to the imidization reaction solvent is preferably 1: (5 to 30), and the imidization rate is preferably 20% or more. From the perspective of ensuring solubility relative to the solvent, it is preferably 90% or less, and more preferably 60% or less. The temperature of the imidization reaction is 0 to 100° C., preferably 20 to 60° C.; the reaction time is 1 to 120 hours, preferably 2 to 30 hours.
[0127] The dehydrating agent may be an acid anhydride compound, such as acetic anhydride, propionic anhydride, or trifluoroacetic anhydride; the molar ratio of the polyamic acid to the dehydrating agent is 1:(1-10). The catalyst may be selected from pyridine, trimethylamine, or triethylamine; the molar ratio of the dehydrating agent to the catalyst is 1:(0.1-5). The imidization rate is a value expressing the ratio of the total number of amic acid structures or amic acid ester structures to the number of imide ring structures in the polyimide as a percentage. Here, a portion of the imide ring may be an isoimide ring.
[0128] The solvent used in the polymerization reaction and the solvent used in the imidization reaction can be the same as or different from the solvent (B) in the liquid crystal alignment agent. There is no particular limitation on the solvent used in the polymerization reaction and the solvent used in the imidization reaction, as long as they can dissolve the reactants. Examples include N,N-methylformamide, N,N-methylacetamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, m-cresol, and tetrahydrofuran.
[0129] Solvent (B)
[0130] The solvent (B) used in the liquid crystal alignment agent of the present invention is a polar aprotic solvent, including N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, m-cresol, and / or tetrahydrofuran. The amount of the solvent (B) used is 0 to 100% by weight.
[0131] Additive (C)
[0132] The liquid crystal alignment agent may optionally contain an additive (C) within the scope of not affecting the efficacy of the present invention, wherein the additive (C) includes an epoxy compound, a leveling agent, or a combination thereof. The additive (C) is used to improve the adhesion of the liquid crystal alignment film to the substrate surface.
[0133] Epoxides
[0134] From the perspective of improving the durability of the liquid crystal alignment film, the liquid crystal alignment agent of the present invention may further contain an epoxy compound as a component other than the polymer (A). The epoxy compound serves to improve the adhesion between the liquid crystal alignment film and the substrate. The epoxy compound is preferably at least one compound represented by formula (Y):
[0135]
[0136] Among them, R 10 Any one or combination independently selected from hydrogen atoms, halogen atoms, alkyl groups with 1 to 6 carbon atoms, alkenyl groups with 2 to 6 carbon atoms, alkynyl groups with 2 to 6 carbon atoms, monovalent organic groups with 1 to 6 carbon atoms containing fluorine atoms, and / or phenyl groups. 11 R is independently selected from hydrogen atom, alkyl group with 1 to 6 carbon atoms, 11 Preferably it is a hydrogen atom. 12 are independently selected from monovalent or divalent organic groups. n is an integer of 1 to 6. The following compounds of formula (Y-1) to formula (Y-5) are preferred examples of the epoxy compound.
[0137]
[0138] When an epoxy compound is used, the amount of the epoxy compound used is 1 to 30%, preferably 2 to 20%, more preferably 2 to 15%, and even more preferably 2 to 10%, by weight relative to the total amount of the polymer (A).
[0139] Leveling agent
[0140] From the perspective of improving the coating properties of the liquid crystal alignment agent, the liquid crystal alignment agent of the present invention may further contain a leveling agent represented by the following structural formula:
[0141]
[0142] Among them, R 13 R is independently selected from any one or combination of alkyl groups having 1 to 12 carbon atoms. 14Independently selected from one or a combination of -OH and -O. Examples of leveling agents include ethyl acetate, ethylene glycol monobutyl ether, diethylene glycol diethyl ether, diacetone alcohol, and ethylene glycol butyl ether acetate. When a leveling agent is used, the amount of the leveling agent used is 0 to 80% by weight relative to the total weight of polymer (A).
[0143] Preparation method of liquid crystal alignment agent
[0144] The preparation method of the liquid crystal alignment agent is not particularly limited and can be prepared using a common mixing method. For example, a solvent (B) and optionally an additive (C) are added to a polymer (A) at a temperature between 0°C and 200°C, and stirring is continued until dissolved. Preferably, the solvent (B) is added to the polymer (A) at a temperature between 20°C and 60°C.
[0145] Liquid crystal alignment film and method for manufacturing liquid crystal display element
[0146] By using the above-mentioned liquid crystal alignment agent, a liquid crystal alignment film can be manufactured. In addition, the liquid crystal display element of the present invention is manufactured using the liquid crystal alignment film formed by the above-mentioned liquid crystal alignment agent. There is no particular limitation on the operating mode of the liquid crystal display element of the present invention. For example, it can be applicable to various operating modes such as TN (Twisted Nematic) type, STN type, vertical alignment type (including VA-MVA type, VA-PVA type, etc.), in-plane switching type (IPS type), FFS (Fringe Field Switching) type, and optically compensated bend type (OCB type).
[0147] The liquid crystal display device of the present invention can be produced, for example, by the following steps 1.1 to 1.5. In step 1.1, the substrate used varies depending on the desired operation mode. Steps 1.2 to 1.5 are common to each operation mode.
[0148] 1.1 Coating
[0149] First, the liquid crystal alignment agent of the present invention is coated on the substrate, and then a coating film is formed on the substrate by heating the coated surface. The coating method is implemented by, but not limited to, a relief printing process (APR COATING), spin coating (SPINCOATING), spray coating (INKJET PRINTING), etc. Generally, materials such as glass, flexible PET film, and flexible PI film with a transparent conductive film with an etched pattern are used as the substrate material of the PI liquid crystal alignment film. As the substrate base material, for example, float glass, soda-lime glass, borosilicate glass can be used; or a transparent substrate made of plastics such as polyethylene terephthalate, polybutylene terephthalate, polyethersulfone, polycarbonate, PET, and PI flexible film. The transparent conductive film on the substrate material can be an indium tin oxide or other transparent metal oxide coating, and a pattern is formed by photolithography.
[0150] 1.2 Pre-baking
[0151] After applying the liquid crystal alignment agent, the substrate with the film layer needs to be pre-baked. This is primarily to volatilize the solvent and convert the film layer from a wet film to a dry film. The pre-baking temperature is preferably 30-200°C, more preferably 60-150°C, and particularly preferably 60-120°C. The pre-baking time is preferably 0.25-30 minutes, more preferably 0.5-8 minutes. For example, the pre-baking temperature is 80-110°C for 1-8 minutes.
[0152] 1.3 Curing process
[0153] One purpose of curing is to completely remove the solvent, while another is to thermally imidize the amic acid structures present in the polymer. The primary curing temperature is preferably 80-300°C, more preferably 100-300°C, and particularly preferably 100-250°C. The primary curing time is preferably 5-200 minutes, more preferably 10-100 minutes, and particularly preferably 15-60 minutes. The curing equipment used includes, but is not limited to, high-temperature ovens, vacuum ovens, hot plate curing ovens, infrared radiation curing ovens, and the like.
[0154] The thickness of the film layer after coating and drying of the present invention is 50 to 200 nm, preferably 80 to 150 nm, and more preferably 80 to 120 nm.
[0155] 1.4 Alignment process
[0156] When manufacturing TN type, STN type, IPS type, OCB type or FFS type liquid crystal display elements, the coating film formed in the above step 1.3 is subjected to a treatment to impart liquid crystal orientation ability. As a result, the coating film is given the orientation ability of the liquid crystal molecules and becomes a liquid crystal alignment film. As a treatment to impart orientation ability, for example, there can be listed: winding a cloth made of fibers such as nylon, rayon, cotton, etc. on a roller, and rubbing the coating film in a certain direction with the roller; or irradiating the coating film with polarized light or non-polarized light radiation for optical orientation treatment. On the other hand, when manufacturing a VA type liquid crystal display element, the coating film formed in the above step 1.3 can be used directly as a liquid crystal alignment film, or the coating film can be subjected to a treatment to impart orientation ability.
[0157] When the coating film is given liquid crystal orientation ability by photo-orientation treatment, as the radiation irradiating the coating film, for example, ultraviolet rays and visible light containing wavelengths of 150 to 800 nm, preferably ultraviolet rays of 200 to 400 nm can be used. When the radiation is polarized light, it can be linearly polarized light or partially polarized light. In addition, when the radiation used is linearly polarized light or partially polarized light, it can be irradiated from a direction perpendicular to the surface of the substrate, or it can be irradiated from an oblique direction, or it can be irradiated in combination. In the case of irradiating non-polarized radiation, the irradiation direction is set to an oblique direction. As the light source used, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. Ultraviolet rays in a preferred wavelength range can be obtained by using a light source together with, for example, a filter, a diffraction grating, etc. The irradiation amount of the radiation is preferably 10 to 5000 mJ / cm 2 , more preferably 30 to 2000 mJ / cm 2 . In addition, in order to improve the reactivity, the coating film can be irradiated with light while being heated. The heating temperature is generally 30 to 250°C, preferably 40 to 200°C, and more preferably 50 to 150°C. In addition, when ultraviolet rays containing light with a wavelength of 150 to 800 nm are used, the light-irradiated film obtained in the above process can be used directly as a liquid crystal alignment film, but the light-irradiated film can also be fired. The firing temperature at this time is preferably 80 to 300°C, and more preferably 120 to 250°C. The firing time is preferably 5 to 200 minutes, and more preferably 10 to 100 minutes. The photo-alignment treatment here is equivalent to a photo-irradiation treatment in a state where it is not in contact with the liquid crystal layer.
[0158] It should be noted that the liquid crystal alignment film after the brushing treatment can also be treated as follows: by irradiating a portion of the liquid crystal alignment film with ultraviolet light, thereby changing the pretilt angle of a portion of the liquid crystal alignment film; or forming a resist film on a portion of the surface of the liquid crystal alignment film, and then performing a brushing treatment in a direction different from the previous brushing treatment, and then removing the resist film, so that the liquid crystal alignment film has different liquid crystal alignment capabilities in each region. In this case, the viewing angle characteristics of the resulting liquid crystal display element can be improved. The liquid crystal alignment film suitable for VA type liquid crystal display elements can also be suitable for PSA (Polymer Sustained Alignment) type liquid crystal display elements.
[0159] 1.5 Construction of Liquid Crystal Display Element
[0160] After successfully manufacturing a substrate with a PI liquid crystal alignment film, a SPACER is used as a support between the two substrates. The SPACER can be a PHOTOSPACER, a homogeneous equal-size silicon ball, or a homogeneous equal-size plastic microsphere, etc., with a particle size of preferably 3 to 20 μm, more preferably 4 to 15 μm, and more preferably 5 to 10 μm. The frame uses a sealant as a sealing material. The sealant can be a heat-curing epoxy resin or a UV-curing acrylic resin. The sealant generally contains supporting microspheres of corresponding sizes, such as homogeneous equal-size silicon balls or homogeneous equal-size plastic microspheres, with a particle size of preferably 3 to 20 μm, more preferably 4 to 15 μm, and more preferably 5 to 10 μm.
[0161] Liquid crystal can be filled between the two substrates using a vacuum infusion machine, direct droplet addition via an ODF process, or direct spraying. Different types of liquid crystals are used depending on the display mode, including IPS, FFS, TN, STN, VA, OCB, and other liquid crystals, as well as liquid crystals with specific characteristics. The two substrates, which have undergone the above processes, are bonded together using precision laminating equipment, with the PI alignment film sides facing each other. The lamination angle is determined by the display mode of the LCD, ensuring that the light alignment directions of the two substrates form a specific angle required by the display mode. For example, FFS and IPS can be bonded with the two substrates aligned in either the same or opposite orientation directions, while the TN mode uses two substrates aligned at a 90° angle.
[0162] After the liquid crystal is filled and the frame sealant is cured, a liquid crystal display with a uniform cell thickness is formed, which can be post-baked and the substrate can be cut as needed.
[0163] The liquid crystal display of the present invention may or may not require attachment of a polarizer, depending on the display mode. Examples of the polarizer include a polarizing film sandwiched between cellulose acetate protective films, where the polarizing film is a so-called "H film" made by stretching and orienting polyvinyl alcohol while allowing it to absorb iodine, or a polarizer made of the H film itself.
[0164] At this point, it is connected to the relevant device by binding IC, FPC or inserting PIN, or directly connecting with pins, or bonding with conductive materials, or soldering, so as to obtain the corresponding display content under the drive of electrical signals.
[0165] The liquid crystal display element of the present invention can be effectively applied to various devices, such as timers, calculators, clocks, word processors, laptop computers, automobile central control systems, portable digital devices, mobile phones, various monitors, various LCD televisions, information displays and non-display type LCD panels with special functions (LCD panels with light phase adjustment, light refraction adjustment functions, etc.).
[0166] Example
[0167] The following examples provide detailed descriptions of liquid crystal alignment agents and liquid crystal display devices obtained using the polymers of the present invention. However, the present invention is not limited to these examples, and modifications based on the examples are within the scope of the present invention. The following lists the tetracarboxylic dianhydride, diamine, and solvent used in the Examples and Comparative Examples. The following descriptions may use the compound numbers or abbreviations.
[0168] Tetracarboxylic dianhydride
[0169] Compound represented by formula (G-28): cyclobutanetetracarboxylic dianhydride (CBDA)
[0170]
[0171] Compound represented by formula (G-40-1): 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride
[0172] Basic diamine
[0173] Compound represented by formula (Z-1-1): p-phenylenediamine
[0174]
[0175] Compound represented by formula (Z-11-1): 3,5-diaminobenzoic acid
[0176]
[0177] Compound represented by formula (Z-42-1): 4,4'-diaminodiphenylmethane
[0178]
[0179] Compound represented by formula (Z-77-1): 2,2'-dimethyl-4,4'-diaminobiphenyl
[0180] Alignment structure diamine
[0181] Compound represented by formula (S-3): 2,4-diaminophenyl octadecyl ether
[0182]
[0183] Compound represented by formula (S-4): 4,4-(1,3-propanedioxy)diphenylamine
[0184] Compound represented by formula (S-5): dihydrocholesterol 3,5-diaminobenzoate
[0185] Compound represented by formula (S-6): 4-(4-octadecyl ether-1-piperazinyl)-1,3-phenylenediamine
[0186] Compound represented by formula (S-7): 4,4-bis(1,3-propylenedioxypiperidinyl)diphenylamine
[0187] Compound represented by formula (S-8): 5-(4-dihydrocholesterol-1-piperazinyl)-1,3-phenylenediamine
[0188]
[0189] Compound represented by formula (S-9): 4-(4-octadecylcarboxamide-1-piperazinyl)-1,3-phenylenediamine
[0190]
[0191] Compound represented by formula (S-10): 4-(4-(4'-pentyl-[1,1'-bis(cyclohexyl)])phenylpiperazinyl)-1,3-diamine
[0192]
[0193] Solvent (B)
[0194] Solvent ingredients: N-methyl-2-pyrrolidone (NMP), ethylene glycol monobutyl ether (BC)
[0195] (1) Preparation Example of Liquid Crystal Alignment Agent
[0196] Preparation Example 1 (hereinafter referred to as PAA-1)
[0197] At room temperature, under nitrogen atmosphere, 9.72g (0.09mol) of the basic diamine compound represented by formula (Z-1-1) (hereinafter referred to as Z-1-1), 4.60g (0.01mol) of the diamine compound represented by the alignment structure represented by formula (S-6) (hereinafter referred to as S-6) and 79.2g of N-methyl-2-pyrrolidone (hereinafter referred to as NMP) were added to a 1L three-necked round-bottom flask in sequence, and stirred at room temperature for 30 minutes to confirm complete dissolution. Then 19.6g (0.1mol) of the tetracarboxylic dianhydride compound represented by formula (G-28) (hereinafter referred to as G-28) was added, and the reaction was stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, 186.6g of NMP and 265.7g of ethylene glycol monobutyl ether (hereinafter referred to as BC) were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC=50 / 50 (weight ratio).
[0198] Preparation Example 2 (hereinafter referred to as PAA-2)
[0199] At room temperature and under a nitrogen atmosphere, 19.72 g (0.09 mol) of Z-1-, 4.24 g (0.01 mol) of the diamine compound having the alignment structure represented by formula (S-7) (hereinafter referred to as S-7), and 78.3 g of NMP were added to a 1L three-necked round-bottom flask in sequence. The mixture was stirred at room temperature for 30 minutes to confirm complete dissolution. 19.6 g (0.1 mol) of G-28 was then added, and the mixture was stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, 184.6 g of NMP and 262.9 g of BC were diluted and stirred to obtain a transparent, viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0200] Preparation Example 3 (hereinafter referred to as PAA-3)
[0201] At room temperature and under a nitrogen atmosphere, 18.64 g (0.08 mol) of Z-1-, 12.76 g (0.02 mol) of a diamine compound having an alignment structure represented by formula (S-8) (hereinafter referred to as S-8), and 95.7 g of NMP were added to a 1L three-necked round-bottom flask in sequence. The mixture was stirred at room temperature for 30 minutes to confirm complete dissolution. 19.6 g (0.1 mol) of G-28 was then added, and the mixture was stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, the mixture was diluted with 225.5 g of NMP and 321.2 g of BC, respectively, and stirred to obtain a transparent, viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0202] Preparation Example 4 (hereinafter referred to as PAA-4)
[0203] At room temperature, under a nitrogen atmosphere, 13.68g (0.09mol) of the basic diamine compound represented by the formula (Z-11-1) (hereinafter referred to as Z-11-1), 4.60g (0.01mol) of S- and 101.5g of NMP were added to a 1L three-necked round-bottom flask, stirred at room temperature for 30 minutes, and confirmed to be completely dissolved. 25.22g (0.1mol) of the tetracarboxylic dianhydride compound represented by the formula (G-40-1) (hereinafter referred to as G-40-1) was then added, and the reaction was stirred at room temperature for 3 hours to obtain a polyamic acid polymer having a reaction solid content of 30%. After the reaction was completed, NMP 239.3g and BC 340.8g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent having a solid content of 6% and a solvent ratio of NMP / BC=50 / 50 (weight ratio).
[0204] Preparation Example 5 (hereinafter referred to as PAA-5)
[0205] At room temperature, under a nitrogen atmosphere, Z-11-113.68g (0.09mol), S-74.24g (0.01mol) and NMP 100.7g were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. G-40-125.22g (0.1mol) was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 237.3g and BC 337.9g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0206] Preparation Example 6 (hereinafter referred to as PAA-6)
[0207] At room temperature, under a nitrogen atmosphere, Z-11-112.16g (0.08mol), S-812.76g (0.02mol) and NMP 117.0g were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. G-40-125.22g (0.1mol) was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 275.8g and BC 392.8g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0208] Preparation Example 7 (hereinafter referred to as PAA-7)
[0209] At room temperature and under a nitrogen atmosphere, 17.82 g (0.09 mol) of the base diamine compound represented by formula (Z-42-1), 4.60 g (0.01 mol) of S-6, and 98.1 g of NMP were added to a 1L three-necked round-bottom flask in sequence. The mixture was stirred at room temperature for 30 minutes to confirm complete dissolution. 19.6 g (0.1 mol) of G-28 was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, 231.1 g of NMP and 329.2 g of BC were diluted and stirred to obtain a transparent, viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0210] Preparation Example 8 (hereinafter referred to as PAA-8)
[0211] At room temperature and under a nitrogen atmosphere, 19.72 g (0.09 mol) of Z-1-, 4.87 g (0.01 mol) of a diamine compound having an alignment structure represented by formula (S-9) (hereinafter referred to as S-9), and 79.8 g of NMP were added to a 1L three-necked round-bottom flask in sequence. The mixture was stirred at room temperature for 30 minutes to confirm complete dissolution. 19.6 g (0.1 mol) of G-28 was then added, and the mixture was stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, the mixture was diluted with 188.1 g of NMP and 267.9 g of BC, respectively, and stirred to obtain a transparent, viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC of 50 / 50 (weight ratio).
[0212] Preparation Example 9 (hereinafter referred to as PAA-9)
[0213] At room temperature and under a nitrogen atmosphere, 18.64 g (0.08 mol) of Z-1-1, 10.048 g (0.02 mol) of the diamine compound with the alignment structure represented by formula (S-10) (hereinafter referred to as S-10), and 89.3 g of NMP were added to a 1L three-necked round-bottom flask in sequence. The mixture was stirred at room temperature for 30 minutes to confirm complete dissolution. 19.6 g (0.1 mol) of G-28 was then added, and the mixture was stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, 210.6 g of NMP and 299.9 g of BC were diluted and stirred to obtain a transparent, viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0214] Preparation Example 10 (hereinafter referred to as PAA-10)
[0215] At room temperature, under nitrogen atmosphere, 19.08g (0.09mol) of the basic diamine compound represented by formula (Z-77-1) (hereinafter referred to as Z-77-1), 4.60g (0.01mol) of S-6, and 114.1g of NMP were added to a 1L three-necked round-bottom flask in sequence, stirred at room temperature for 30 minutes, and confirmed to be completely dissolved. Then 125.22g (0.1mol) of G-40- was added, and the mixture was stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, 269.0g of NMP and 383.1g of BC were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0216] Preparation Example 11 (hereinafter referred to as PAA-11)
[0217] At room temperature, under a nitrogen atmosphere, Z-11-113.68g (0.09mol), S-94.87g (0.01mol) and NMP 102.1g were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. G-40-125.22g (0.1mol) was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 240.8g and BC 342.9g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0218] Preparation Example 12 (hereinafter referred to as PAA-12)
[0219] At room temperature, under a nitrogen atmosphere, Z-11-112.16g (0.08mol), S-1010.048g (0.02mol) and NMP 110.7g were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. G-40-125.22g (0.1mol) was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 260.9g and BC 371.5g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0220] Preparation Example 13 (hereinafter referred to as PAA-13)
[0221] At room temperature, under nitrogen atmosphere, Z-1-15.4g (0.05mol), S-623g (0.05mol) and NMP 157.07g were added to a 1L three-necked round-bottom flask in sequence, stirred at room temperature for 30 minutes, and confirmed to be completely dissolved. Then, G-2819.6g (0.1mol) was added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 370.07g and ethylene glycol monobutyl ether (hereinafter referred to as BC) 527.14g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0222] Preparation Example 14 (hereinafter referred to as PAA-14)
[0223] At room temperature and under a nitrogen atmosphere, 16.48 g (0.06 mol) of Z-1-1, 16.96 g (0.04 mol) of S-7, and 131.47 g of NMP were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. 19.6 g (0.1 mol) of G-28 was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, 309.96 g of NMP and 441.43 g of BC were diluted and stirred to obtain a transparent, viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0224] Preparation Example 15 (hereinafter referred to as PAA-15)
[0225] At room temperature, under a nitrogen atmosphere, Z-1-110.692g (0.099mol), S-80.638g (0.001mol) and NMP 50.667g were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. G-2819.6g (0.1mol) was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 119.389g and BC 170.056g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0226] Preparation Example 16 (hereinafter referred to as PAA-16)
[0227] At room temperature, under nitrogen atmosphere, Z-11-113.68g (0.09mol), S-69.66g (0.021mol) and NMP 129.60g were added to a 1L three-necked round-bottom flask in sequence, stirred at room temperature for 30 minutes, and confirmed to be completely dissolved. Then 25.22g (0.1mol) of the tetracarboxylic dianhydride compound represented by formula (G-40-1) (hereinafter referred to as G-40-1) was added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 305.54g and BC 435.14g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0228] Preparation Example 17 (hereinafter referred to as PAA-17)
[0229] At room temperature, under a nitrogen atmosphere, Z-11-113.68g (0.09mol), S-714.84g (0.035mol) and NMP 160.26g were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. G-40-125.22g (0.1mol) was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, 377.67g NMP and 537.93g BC were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0230] Preparation Example 18 (hereinafter referred to as PAA-18)
[0231] At room temperature, under a nitrogen atmosphere, Z-11-112.16g (0.08mol), S-828.71g (0.045mol) and NMP 191.89g were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. G-40-125.22g (0.1mol) was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 452.32g and BC 644.21g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0232] Comparative Preparation Example 1 (hereinafter referred to as PAA-19)
[0233] At room temperature and under a nitrogen atmosphere, 19.72 g (0.09 mol) of Z-1-, 3.76 g (0.01 mol) of the diamine compound represented by formula (S-3) (hereinafter referred to as S-3), and 77.2 g of NMP were added to a 1L three-necked round-bottom flask in sequence. The mixture was stirred at room temperature for 30 minutes to confirm complete dissolution. 19.6 g (0.1 mol) of G-28 was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, 181.9 g of NMP and 259.1 g of BC were diluted and stirred to obtain a transparent, viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0234] Comparative Preparation Example 2 (hereinafter referred to as PAA-20)
[0235] At room temperature and under a nitrogen atmosphere, 19.72 g (0.09 mol) of Z-1-, 2.58 g (0.01 mol) of the diamine compound represented by formula (S-4) (hereinafter referred to as S-4), and 74.4 g of NMP were added to a 1L three-necked round-bottom flask in sequence. The mixture was stirred at room temperature for 30 minutes to confirm complete dissolution. 19.6 g (0.1 mol) of G-28 was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, 175.5 g of NMP and 249.9 g of BC were diluted and stirred to obtain a transparent, viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0236] Comparative Preparation Example 3 (hereinafter referred to as PAA-21)
[0237] At room temperature and under a nitrogen atmosphere, 18.64 g (0.08 mol) of Z-1-1, 10.44 g (0.02 mol) of the diamine compound represented by formula (S-5) (hereinafter referred to as S-5), and 90.3 g of NMP were added to a 1L three-necked round-bottom flask in sequence. The mixture was stirred at room temperature for 30 minutes to confirm complete dissolution. 19.6 g (0.1 mol) of G-28 was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, 212.7 g of NMP and 303.0 g of BC were diluted and stirred to obtain a transparent, viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0238] Comparative Preparation Example 4 (hereinafter referred to as PAA-22)
[0239] At room temperature, under a nitrogen atmosphere, Z-11-113.68g (0.09mol), S-33.76g (0.01mol) and NMP 99.5g were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. G-40-125.22g (0.1mol) was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 234.6g and BC 334.2g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0240] Comparative Preparation Example 5 (hereinafter referred to as PAA-23)
[0241] At room temperature, under a nitrogen atmosphere, Z-11-113.68g (0.09mol), S-42.58g (0.01mol) and NMP 96.8g were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. G-40-125.22g (0.1mol) was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 228.2g and BC 324.9g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0242] Comparative Preparation Example 6 (hereinafter referred to as PAA-24)
[0243] At room temperature, under a nitrogen atmosphere, Z-11-112.16g (0.08mol), S-510.44g (0.02mol) and NMP 111.6g were added to a 1L three-necked round-bottom flask in sequence and stirred at room temperature for 30 minutes to confirm complete dissolution. G-40-125.22g (0.1mol) was then added and stirred at room temperature for 3 hours to obtain a polyamic acid polymer with a reaction solid content of 30%. After the reaction was completed, NMP 263.0g and BC 374.6g were diluted and stirred to obtain a transparent viscous polyamic acid solution liquid crystal alignment agent with a solid content of 6% and a solvent ratio of NMP / BC = 50 / 50 (weight ratio).
[0244] The types and molar ratios of monomers used in the polyamic acid reaction in Liquid Crystal Alignment Agent Preparation Examples 1-18 and Comparative Preparation Examples 19-24 are shown in Table 1.
[0245] Table 1 Monomer types and molar ratios used in polyamic acid reactions in preparation examples and comparative preparation examples
[0246]
[0247] Example 1
[0248] In the embodiments of the present invention, only IPS and FFS type liquid crystal display elements are used to explain the present invention, but the present invention is not limited thereto.
[0249] The liquid crystal alignment agent prepared in Preparation Example 1 was applied to a first glass substrate having an IPS (in-plane switching) or FFS (fringe field switching) ITO electrode by spin coating to form a pre-coating layer. After pre-baking (hot plate curing oven, 85°C, 6 minutes), curing (high temperature oven, 225°C, 50 minutes), and alignment exposure (254nm polarized light, 5mW / cm 2 , 500mJ / cm 2 ) to obtain a first glass substrate having an ITO electrode and on which the liquid crystal alignment film of Preparation Example 1 is formed.
[0250] The liquid crystal alignment agent of Preparation Example 1 was applied to a second glass substrate without an ITO electrode by spin coating to form a pre-coating layer. The above pre-baking, curing, and alignment exposure steps were repeated to obtain the second glass substrate having the liquid crystal alignment film of Preparation Example 1 formed thereon.
[0251] A UV-curable acrylic resin sealant is applied to the periphery of the first glass substrate, leaving an inlet for the liquid crystal liquid, and a plastic microsphere spacer with an equal particle size of 6 μm is sprinkled on the second glass substrate. Then, the two glass substrates are bonded in an anti-parallel manner to the orientation direction (5 kg external force for 30 minutes), and the sealant is cured. Next, the liquid crystal is injected, the liquid crystal injection port is sealed with ultraviolet light curing glue, and the ultraviolet light curing glue is hardened with ultraviolet light, and then polarizers are attached to the outer sides of the two glass substrates, thereby preparing an IPS or FFS type liquid crystal display element of embodiment 1. The photoelectric performance of the liquid crystal box obtained in this embodiment is evaluated, and the results are shown in Table 2, the characterization data of the embodiment and the comparative example.
[0252] Example 2-18
[0253] Examples 2-18 of liquid crystal alignment films and liquid crystal display elements were prepared using the same process steps as Example 1, except that the liquid crystal alignment agent used in Examples 2-18 was replaced with the liquid crystal alignment agent prepared in Preparation Example 2-18. Finally, the photoelectric performance of the liquid crystal cells obtained in Examples 2-18 was evaluated. The results are shown in Table 2, Characterization Data for Examples and Comparative Examples.
[0254] Comparative Examples 1-6
[0255] Comparative Examples 1-6 of liquid crystal alignment films and liquid crystal display elements were prepared using the same process steps as Example 1, except that the liquid crystal alignment agent used in Comparative Examples 1-6 was replaced with the liquid crystal alignment agent prepared in Comparative Preparation Examples 1-6. Finally, the photoelectric performance of the liquid crystal cells obtained in Comparative Examples 1-6 was evaluated. The results are shown in Table 2, Characterization Data for the Examples and Comparative Examples.
[0256] Performance evaluation method
[0257] (1) Characterization of liquid crystal orientation
[0258] The liquid crystal display elements produced in the examples and comparative examples were observed using an optical microscope at 50x magnification to determine the presence or absence of abnormal regions of light-dark changes when a voltage of 5 V was applied and released. A situation where no abnormal region was observed was considered "good" for the liquid crystal orientation, while a situation where an abnormal region was observed was considered "poor" for the liquid crystal orientation.
[0259] Testing equipment: Optical microscope
[0260] Voltage supply equipment: signal generator
[0261] (2) Characterization of the electrical properties of the liquid crystal cell
[0262] Testing equipment: Dongyang Technology Co., Ltd. "6254C Liquid Crystal Physical Property Evaluation System"
[0263] Voltage holding ratio (VHR) measurement conditions: voltage 5V, pulse width 60us / frame, period 1667ms, measurement temperature 23℃ / 90℃.
[0264] (3) Characterization of liquid crystal cell pretilt angle
[0265] Test equipment: Pretilt angle meter; Shintech Optitro-STD (3STN1 1); OPTIPRO LCD optical test system
[0266] Test wavelength: 591.4nm
[0267] Test mode: TN / VA / IPS mode
[0268] (4) Characterization of liquid crystal cell stability
[0269] AC aging equipment: signal generator; parameter setting: ±14V AC aging 72Hrs, 30Hz, square wave, room temperature + backlight
[0270] High temperature and high humidity aging equipment: constant temperature test chamber; parameter setting: 85℃ / 85%RH aging 72Hrs
[0271] Evaluation results of pretilt angle stability:
[0272] T1: ΔPretilt Angle < 0.1°, good stability
[0273] T2: ΔPretilt Angle is between 0.1-0.5°, and the stability is average
[0274] T3: ΔPretilt Angle>0.5°, poor stability
[0275] (5) Characterization of the resistivity of liquid crystal alignment films
[0276] Test equipment: Electrometer / high resistance meter (KEYSIGHT B2985A), sample thickness 5-50 μm, active area 30-60 cm 2
[0277] Test parameters: Voltage measurement range 1μV-20V, 0.01fA measurement resolution, 2000 readings / s.
[0278] Table 2 Characterization data of examples and comparative examples
[0279]
[0280] Through the above data characterization and analysis, compared with the prior art, the liquid crystal alignment agent of the present invention significantly enhances the anchoring ability of the liquid crystal alignment film to the liquid crystal due to the presence of a diamine residue with a specific piperazine or piperidine group. After exposure and alignment, the liquid crystal alignment film of the present invention makes the liquid crystal orientation more uniform and stable, without any defects, and reduces the level of AC afterimages caused by insufficient anchoring force on the LCD panel, thereby improving the contrast of the LCD panel and effectively improving the display effect of the liquid crystal display. In addition, the diamine monomer with a specific piperazine or piperidine group used in the liquid crystal alignment agent of the present invention has a good ability to conduct electrons, the volume resistivity of the liquid crystal alignment film is low, and the dissipation of the DC bias charge in the LCD box is accelerated, thereby effectively reducing the afterimage and flicker problems caused by the accumulation of DC bias charge on the LCD panel. In addition, after AC and high temperature and high humidity aging tests, the liquid crystal alignment film of the present invention has a stable orientation effect, excellent pretilt angle stability, and excellent reliability, making it suitable for large-scale promotion and application.
[0281] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A liquid crystal alignment agent, characterized in that: include: A polymer (A) and a solvent (B), wherein the polymer (A) is obtained by reacting a mixture, wherein the mixture comprises a tetracarboxylic dianhydride component (a) and a diamine component (b), wherein the diamine component (b) comprises an alignment structure diamine (b-1) and a base diamine (b-2), and the alignment structure diamine (b-1) is selected from any one or a combination of compounds represented by formula (1), formula (2) and / or formula (3); wherein R7 independently represents any one or combination of -O-, -COO, -OCH2, -COOCH2, -CH2OCO, -CH2O, -NHCO, -CONH, -N(CH3)CO, olefin, alkyne, benzene ring, cyclohexane, and imide ring; R8 independently represents an alkyl chain having 1 to 50 carbon atoms; S1 independently represents any one or combination of the structures represented by formula (S-1) and / or formula (S-2); 2. The liquid crystal alignment agent according to claim 1, wherein The tetracarboxylic dianhydride component (a) is selected from any one or combination of compounds represented by formula (a-1) and / or formula (a-2); Wherein, G1 is an aliphatic, alicyclic or aromatic organic group.
3. The liquid crystal alignment agent according to claim 1, wherein The base diamine (b-2) is selected from at least one compound represented by formula (4); Wherein, X1 and X2 independently represent any one or a combination of a hydrogen atom, an alkyl chain with 1 to 10 carbon atoms, an alkenyl chain with 2 to 10 carbon atoms, and an alkynyl chain with 2 to 10 carbon atoms; and Z1 is a divalent organic group.
4. The liquid crystal alignment agent according to claim 1, wherein The polymer (A) is any one or a combination of polyimide, polyamic acid and / or polyamic acid ester; based on 100% by weight of the total amount of the liquid crystal alignment agent, the weight percentage of the polymer (A) is 1 to 15%.
5. The liquid crystal alignment agent according to claim 1, wherein The solvent (B) is any one or a combination of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, m-cresol and / or tetrahydrofuran; based on the total amount of the liquid crystal alignment agent as 100 weight%, the weight percentage of the solvent (B) is 0 to 100%.
6. The liquid crystal alignment agent according to claim 1, characterized in that: The liquid crystal alignment agent further comprises at least one compound represented by formula (Y); Among them, R 10 Each independently selected from any one or combination of a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, and / or a phenyl group; R 11 Each is independently selected from any one or combination of a hydrogen atom and an alkyl group having 1 to 6 carbon atoms; R 12 Independently selected from monovalent or divalent organic groups; n is an integer of 1 to 6; based on the total amount of the liquid crystal alignment agent being 100 weight %, the weight percentage of the compound represented by formula (Y) is 1 to 30 weight %.
7. The liquid crystal alignment agent according to claim 1, wherein The molar ratio of the diamine component (b) to the tetracarboxylic dianhydride component (a) in the mixture is 100:(80-100); based on the total amount of the diamine component (b) being 100 mol%, the base diamine is 50 mol%-100 mol%, and the alignment structure diamine is 1 mol%-50 mol%.
8. The liquid crystal alignment agent according to claim 1, wherein In the alignment structure diamine, R7 independently represents any one or a combination of -O-, -COO, -NHCO, -CONH, a benzene ring, a cyclohexane ring, and an imide ring.
9. A liquid crystal alignment film, characterized in that: The liquid crystal alignment film is prepared from the liquid crystal alignment agent according to any one of claims 1 to 8.
10. A liquid crystal display element, characterized in that: The liquid crystal display element includes the liquid crystal alignment film according to claim 9.